The Role of Accounting Profession in the Fight Against Corruption - Miti, Mirela; Çika , Nertila; Dhamo, Sotiraq (European Journal of Multidisciplinary Studies, 2022)
Corruption is the main word of many discussions in developing countries. In the time of globalization and cially the current time of digitalization, corruption is found in many dimensions. Like many countries, Albania in the last decade has undertaken reforms to develop the regulatory framework for the fight against corruption. The perspective on corruption is different and it sometimes appears as a qualitative element as well as a quantitative one, but its effects are undoubtedly an obstacle to the economic development of a cory, as well as damage the integrity causing the loss of the trust of the public. In this context, through our paper, we want to show the role of the accounting profession, in the fight against corruption and the steps taken in the field of accounting, especially in our country, and the innovations that can appear while performing the accounting profession. Currently, IFAC, through the "Action plan for fighting corruption and economic crime" (2022), has provided a conceptual framework, to improve the role of the accounting profession in the fight against corruption, aiming for alignment with the UN SDGs. Albania has also undertaken its reforms in several areas such as the tax system, the justicesystem, the police, financial reporting and accounting and auditing professions, etc., focusing on strengthening institutions, increasing public trust involving professionals with integrity and a high level of professionalism. But the future of every country depends not simply on the establishment and development of legal acts, but above all it will depend on everyone’s awareness, so that with the professionalism that characterizes it, it can lead to a safe and honest future. In the paper, we will first present the framework of the role of the accounting profession in the fight against corruption in Albania, "gangrene" which keeps on increasing, continuing with the empirical and statistical analysis through which it will be understood what the current situation in Albania in the initiative undertaken to fight against corruption. At the end, suggestions are presented for the main actors regarding the role of the accounting profession in the fight against corruption, including it as a main tool.